ДИФФУЗИОН ТЕХНОЛОГИЯ БИЛАН GexSi1-x АСОСИДА ГЕТЕРО ВА ВАРИЗОН СТРУКТУРА ҲОСИЛ ҚИЛИШ ВА УНИНГ ОПТИК ХУСУСИЯТЛАРИНИ ЎРГАНИШ - Зикриллаев, Н.Ф.; Кушиев, Ғ.А.; Турсунов, О.Б.; Ҳамроқулов, Ш.И. (SCIENCE and SOCIETY, 2022)
The development and creation of solar cells based on GexSi1−x hetero and graded-gap structures is also very interesting. Since the production of such structures based on GexSi1−x with certain parameters and structural allows one to significantly expand the spectral region of sensitivity and allows the creation of new types of photodetectors, sensors, and photocells.